The Relevance of Human Resource Accounting in Indonesia - Andre Alif Hatta Sugiarta; dwy anti; Grisviana Diva Nabilla (Universitas Dinamika, 2023)
The purpose of this study is an effort to manage human resources from the perspective of accounting as assets and investments and show the costs that arise from each human resource activity. This research contributes to human resource management from an accounting perspective. This research emphasizes human resource accounting as assets and capital invested by the business world. The literature review is used as the basis for research methods. The results obtained that human resource accounting has an important role for companies where there are activities that use costs in managing human resources. The role of human resources as company assets and accounting information system supporters can determine company performance, internal control, and human resources as meaningful capital for the company.